2017
DOI: 10.1146/annurev-psych-010416-044131
|View full text |Cite
|
Sign up to set email alerts
|

Memory: Organization and Control

Abstract: A major goal of memory research is to understand how cognitive processes in memory are supported at the level of brain systems and network representations. Especially promising in this direction are new findings in humans and animals that converge in indicating a key role for the hippocampus in the systematic organization of memories. New findings also indicate that the prefrontal cortex may play an equally important role in the active control of memory organization during both encoding and retrieval. Observat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
158
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 203 publications
(172 citation statements)
references
References 149 publications
(186 reference statements)
12
158
0
2
Order By: Relevance
“…In particular, structural MRI studies in humans have revealed steeper age-related decline in hippocampus morphology in men compared to women (Pruessner et al, 2001; Raz et al, 2004a; Li et al, 2014). Given that the hippocampus is especially critical for novel associative memory encoding and retrieval (Diana et al, 2007; Ranganath, 2010; Eichenbaum, 2017), we speculated that the relatively preserved hippocampus GMV would play a more important role in associative memory for novel associations in older women compared with older men, and thus structural volumes of the hippocampus are more likely to be associated with individual differences in associative memory for novel associations in older women but not men. Our results confirmed this speculation by demonstrating that structural volume of the hippocampus could account for inter-individual variations in novel associative memory only in older women.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, structural MRI studies in humans have revealed steeper age-related decline in hippocampus morphology in men compared to women (Pruessner et al, 2001; Raz et al, 2004a; Li et al, 2014). Given that the hippocampus is especially critical for novel associative memory encoding and retrieval (Diana et al, 2007; Ranganath, 2010; Eichenbaum, 2017), we speculated that the relatively preserved hippocampus GMV would play a more important role in associative memory for novel associations in older women compared with older men, and thus structural volumes of the hippocampus are more likely to be associated with individual differences in associative memory for novel associations in older women but not men. Our results confirmed this speculation by demonstrating that structural volume of the hippocampus could account for inter-individual variations in novel associative memory only in older women.…”
Section: Discussionmentioning
confidence: 99%
“…Bidirectional interactions between the hippocampus and the pre-frontal cortex play a critical role in normal memory processing 42 . In this respect, we note that learning deficits were revealed in the mutant mice by manipulations of the environmental context and the reward location, conditions requiring cognitive flexibility, and that the decreased fraction of cells tracking the place reference frame following a shuffling of the local cues during the GOL task (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…First of all, the more than four decades of hippocampal spatial mapping studies have developed alongside an equally productive line of investigations, using a variety of methodological approaches, into the basis of memory in the same brain system 3,[41][42][43][44][45][46][47] . The focus of this review is on the coding of space, but, as we will acknowledge, this does not rule out a broader participation of hippocampal neurons and place cells in representation of experience [48][49][50] .…”
Section: Edvard I Moser May-britt Moser and Bruce L Mcnaughtonmentioning
confidence: 99%
“…Over the years, his position evolved from that of an unafraid and much-needed devil's advocate against the pure spatial map hypothesis towards what is now the general consensus view that spatial coding provides a foundation on top of which sensory and event-specific memory is superimposed, and he became a pioneer in the study of how time and temporal order also play a role. His thinking on hippocampal-cortical interactions in memory organization and control is beautifully summarized in his 2017 Annual Review of Psychology article 47 . intrinsic MEC dynamics but also how external inputs from the hippocampus 242 , the medial septum 181,182 , and locomotor [204][205][206][207]262 and head direction circuits 263 contribute to the emergence of grid patterns (Box 1).…”
Section: In Memoriammentioning
confidence: 99%